Unprecedented September Heatwave in the Yangtze River Basin in 2024 and the Great Exposure Risk to School Students - Xie Tiejun; Ding Ting; Gao Hui; Wang Ji (Atmospheric Science Letters)
ABSTRACT In September 2024, the Yangtze River basin experienced a supremely extreme heatwave that broke historical records from at least 1961 and could have a severe impact on outdoor health of school children. This paper provides a timely analysis of the characteristics of the extreme heatwave in the Yangtze River basin in September 2024, its exposure to the population aged 14 years and below, and the causes that led to its occurrence, as well as its future projections. In September 2024, the regional average heatwave days in the Yangtze River basin reached 7.57 days, and the average daily maximum temperature (Tmax) reached 31.53°C, both of which are much higher than the climatology and exceed the historical records. This supremely heatwave resulted in high exposure of the population aged 14 years and under, with the provinces of Sichuan, Chongqing, Hunan, and Jiangxi exposed to more than 100 million person‐days. The extreme expansion of the South Asian High (SAH) and the Western Pacific Subtropical High (WPSH) may have directly contributed to this supremely heatwave. The CMIP6 projections show that the frequency of extreme heatwaves in September similar to that in 2024 will increase in the future.